2013
DOI: 10.1093/nar/gkt020
|View full text |Cite
|
Sign up to set email alerts
|

UV damage regulates alternative polyadenylation of the RPB2 gene in yeast

Abstract: Alternative polyadenylation (APA) is conserved in all eukaryotic cells. Selective use of polyadenylation sites appears to be a highly regulated process and contributes to human pathogenesis. In this article we report that the yeast RPB2 gene is alternatively polyadenylated, producing two mRNAs with different lengths of 3′UTR. In normally growing wild-type cells, polyadenylation preferentially uses the promoter-proximal poly(A) site. After UV damage transcription of RPB2 is initially inhibited. As transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…4). With exposure to the UV-mimetic 4NQO, the CPD plot shows a shift to RNAs with longer 39 UTRs, similar to that seen by Yu and Volkert (2013). However, it also reveals that a significant amount of the polyadenylated RPB2 transcripts (;38%) in undamaged cells terminate promiscuously within the coding sequence.…”
Section: Analysis Of Poly(a) Site Usagesupporting
confidence: 55%
See 3 more Smart Citations
“…4). With exposure to the UV-mimetic 4NQO, the CPD plot shows a shift to RNAs with longer 39 UTRs, similar to that seen by Yu and Volkert (2013). However, it also reveals that a significant amount of the polyadenylated RPB2 transcripts (;38%) in undamaged cells terminate promiscuously within the coding sequence.…”
Section: Analysis Of Poly(a) Site Usagesupporting
confidence: 55%
“…5B). UV exposure causes damage similar to that of 4NQO, inhibits poly(A) site cleavage in mammalian cells (Kleiman and Manley 2001), and induces a shift to longer transcripts from the yeast RPB2 gene (Yu and Volkert 2013). The 4NQO-induced inhibition of in vitro processing is unlikely to be part of the general environmental stress response as we have shown in previous studies that 39-end formation is not inhibited by heat shock (37°C) for a similar amount of time (Cheng et al 2004;He and Moore 2005;Ghazy et al 2009).…”
Section: Figurementioning
confidence: 65%
See 2 more Smart Citations
“…A recent study reported cold shock conditions to globally influence 3 ′ UTR lengths, which regulates gene expression according to the circadian clock (Liu et al 2013). In addition, APA occurs upon UV-induced damage in yeast (Graber et al 2013;Yu and Volkert 2013) and can stress-dependently influence the expression of specific genes, such as HSP70.3, under heat shock conditions (Kraynik et al 2015). Alternative polyadenylation may thus also globally influence mammalian gene expression in conditions of cellular stress.…”
Section: Introductionmentioning
confidence: 99%